2016
DOI: 10.1002/cncr.29921
|View full text |Cite
|
Sign up to set email alerts
|

Rising population of survivors of oral squamous cell cancer in the United States

Abstract: BACKGROUND:The incidence of oropharyngeal cancer (OPC) and a subset of oral cavity cancer (OCC) is increasing in the United States. To the authors' knowledge, the presumed growing prevalence of survivors of OPC and OCC has not been investigated to date. METHODS: Retrospective analysis of End Results data (1975-2012) estimated changes in incidence, 5-year cause-specific survival, and prevalence for OPC and OCC. Changes in incidence, cause-specific survival and prevalence were estimated by linear regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 45 publications
(115 reference statements)
3
66
1
Order By: Relevance
“…This reversal of incidence trends may represent a transition from tobacco‐related, HPV‐unrelated tumors to predominantly HPV‐related tumors. Our study also showed that OPSCC incidence rates increased in the male population but remained stable in the female population, which is consistent with findings from other studies . These findings support HPV as the most likely driver of the rise in OPSCC incidence rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This reversal of incidence trends may represent a transition from tobacco‐related, HPV‐unrelated tumors to predominantly HPV‐related tumors. Our study also showed that OPSCC incidence rates increased in the male population but remained stable in the female population, which is consistent with findings from other studies . These findings support HPV as the most likely driver of the rise in OPSCC incidence rates.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that incidence rates increased in the white population, whereas incidence rates rose sharply in the black population between 1973 and 1984 and then steadily declined between 1984 and 2013. Previous studies have reported on the racial divergence in incidence trends of oropharyngeal cancer . However, no previous study had reported on the initial rise in OPSCC in the black population.…”
Section: Discussionmentioning
confidence: 97%
“…No recent analysis has included cancers of the hypopharynx, nasal cavity, and nasopharynx to describe current incidence trends of HNSCC overall or of non-oropharyngeal HNSCCs. Prior work has shown a decline in HPV-unrelated cancers of the oral cavity and oropharynx, 1, 14, 15 and a decline in larynx cancer using data up 1997. 16 This analysis is a more accurate representation of the comprehensive changes in incidence for all HPV-unrelated cancers: incidence of non-oropharyngeal HNSCCs consistently declined between 2003-2014 in all subgroups (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, retrospective data have suggested that tonsillectomy (removal of the relevant lymphoid tissue and associated epithelium) reduces the risk of OPC. 48 Given the favorable long-term survival of patients with HPV-16-driven OPC, 49,50 there is interest in decreasing therapeutic intensity with the goal of reducing potential long-term sequelae of therapy. 46 In addition, tonsillectomy has its own inherent risks (life-threatening or catastrophic bleeding), and therefore optimizing the ability to predict the patient's risk of developing HPVdriven OPC becomes paramount, as does demonstrating that the benefits outweigh the harms (including considerations of quality of life and cost-effectiveness).…”
Section: Treatment Of Early (Nonsymptomatic) Lesionsmentioning
confidence: 99%